Hidden economy and its scientific-theoretical foundations and socio-economic consequences. - Toyirjon Tolipov Bohodir Ogli (Zien Journals, 2022)
This article is about the hidden economy and its scientific-theoretical foundations and socioeconomic consequences. General concepts about hidden economic situations are briefly explained.
Keywords: Globalization; society; institutionalism; laundering